Vibrio sp. Bacteria in the Gills and Kidneys of White Snapper Fish (Lates calcalifer) - Irmawati, Yuni; Sudirjo, Fien; Salamun, Sri Mila; Aktaulora, Della (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
White snapper fish Lates calcalifer is one of the leading fishery commodities that has great potential to be developed due to increasing demand. The problems often faced in white snapper fish cultivation are diseases caused by bacterial infections, including Vibrio sp. This research aims to determine the type of bacteria Vibrio sp. Which infects the gills and kidneys of white snapper fish. Bacterial isolation was carried out on fish that were indicated to be experiencing symptoms of vibriosis, and identification using the Microbact Identification System. The results identification of Vibrio sp bacteria in the gills of white snapper fish are Vibrio parahaemolitycus and Vibrio fluvialis, while in the kidneys are the bacteria Vibrio parahaemolyticus and Vibrio vulnificus.